Os impactos de barreiras não tarifárias no comércio internacional de produtos brasileiros - Cardoso, Menanes Chaves Barros (2015)
The technology advance and the easy and fast access of people to the information and the products are contributing to the increase of the trade competition among companies and even among the countries. However, it’s necessary to create controls and measures to ensure the quality of local and imported goods and services for the population, without compromising the competitive market equilibrium. So, the present study evaluates the impacts of Non-Tariff Barriers used by importers of Brazilian products over the Brazilian exports in 2013, in particular the use of the type of technical and sanitary barriers. The use of this tool has increased since it was created and so, with overall decrease of tariffs, it has received more attention from Institutions and policy makers of trade and economy. It was found that there is significant impact of this measure on exported Brazilian goods in general as well as for each type of measure. Controlled by other factors, the impact of the measure is positive that suggests an increase in the exports. This same result was observed in the technical barrier. However, it was observed the opposite in the sanitary barrier, suggesting that this type of measure contributes to decrease the Brazilian exports.